Simulation-Based Performance Analysis Of TCP In Wireless Networks Using TCP Sack And TCP Snoop Approaches - Alqadasi, Hamdee Abdullah Thabet (2008)
The growing popularity of wireless devices used to access the Internet and an increasing use of the TCP/IP protocol suites, indicate that in the near future TCP protocol will be frequently used in the wireless links connecting wireless devices. The characteristics of wireless links are significantly different from characteristics of wired network links because data is frequently lost due to the volatile environment in which wireless links operate. This assumption leads to poor performance of TCP in a wireless environment. In this project, we investigated the impact of implementing two different improvement approaches on the behavior of TCP in wireless networks by comparing the performance of TCP SACK, Snoop TCP and compared them with the performance of TCP Reno as a basis of this comparison. OMNeT++ simulation tools used to perform the simulation experiments. During the course of simulation, throughput and delay (measured congestion window) of TCP in wireless networks have been studied, and two different type of traffic (FTP, HTTP) are generated on same network topology with Two scenario had run for each type of traffic (single flow, compete flow).